Evaluation of fertigation uniformity under a drip irrigation system and its effects on irrigation water management in garlic (Allium sativum L.) - Kabyasree, C; Chinmoy, K S; Barsri, B; Pankaj, B; Bipul, D; Pranjit, B; Boishali, D; Arunjyoti, S; Dimpi, D (Plant Science Today, 2026)
Drip irrigation can save 30–60 % of water and enables the simultaneous application of water and fertilisers through fertigation. A field experiment was conducted for three consecutive rabi seasons (2021–22, 2022–23 and 2023–24) to evaluate the effect of different injector and emitter types on fertigation uniformity in garlic (Allium sativum L.) Three types of emitters and two types of fertiliser injectors were tested to determine their influence on the coefficient of variation (Cv) of water and nutrient application. Results showed that both injector type and emitter manufacturing variability significantly affected fertigation and irrigation uniformity. Across the years, the lowest Cv for fertigation was obtained with the combination of a pressure-compensating emitter (2 lph) and a venturi manifold device, whereas the highest Cv resulted from the combination of drip tape emitter (4 lph) with a hydro-pneumatic pressure pump vessel. Fertigation uniformity improved as Cv decreased. The study also revealed noticeable differences between the Cv of irrigation water and the Cv of fertiliser application, indicating that a system performing well in water distribution does not necessarily ensure uniform fertiliser distribution. Based on the findings, the use of 2 lph pressure-compensating emitters with a venturi manifold device is recommended for achieving higher fertigation uniformity in drip irrigation systems.